Bilateral percutaneous mininephrolithotripsy: simultaneous or staged approach? - S. V. Popov; R. G. Guseinov; I. N. Orlov; V. V. Perepelitsa; I. S. Pazin; A. V. Davydov; D. A. Sytnik (Вестник урологии, 2023)
Introduction. Patients with bilateral nephrolithiasis are a challenge for the treating physician. Therefore, such patients traditionally are subject to phased surgery to reduce the rate of complications. At the same time, the enhancement of endoscopic technologies and anesthesia makes it possible to perform surgical treatment of bilateral nephrolithiasis simultaneously.Objective. To evaluate the effectiveness and safety of performing simultaneous bilateral percutaneous nephrolithotripsy (PCNL).Materials & methods. The main group comprises 19 patients (avg age 45.0 ± 2.25 years) suffering from bilateral nephrolithiasis (13 men and 6 women). The control group include 20 patients (avg age 45.80 ± 2.29 years) suffering from bilateral nephrolithiasis. Main group patients underwent simultaneous bilateral mini-PCNL, control group patients — staged PCNL within two hospitalisations. The visual analogue scale (VAS) was used to assess the pain severity. Patients noted subjective pain sensations on post-op days 1 and 3. QoL indicators were assessed using the SF-36 general questionnaire, as well as the Russian-language validated version of the WISQoL questionnaire.Results. There were no statistically significant differences between the parameters (the difference between the hemoglobin before and after mini-PCNL was 12 g/l; between the serum creatinine was 18 µmol/l). There was a decrease in total surgery time (121.0 ± 6.1 min) for main group patients compared to (147.0 ± 7.3 min) control group patients (total surgery time during the first and second hospitalisations) and a reduction in hospital stay (4.50 ± 0.23 days) for main group patients compared to control group patients (10.0 ± 0.5 days). Complications observed by us in the two groups were comparable. The valuesobtained on the SF, RE and MH scales in main group patients were higher both on post-op day 1 (67.9 ± 3.39; 56.90 ± 2.85 and 63.80 ± 3.19, respectively) and post-op day 3 (86.80 ± 4.34; 83.70 ± 4.19 and 82.50 ± 4.13, respectively) compared to control group patients during the first and second hospitalizations. Statistically significant differences were also recorded according to the grades "Social functioning" and "Emotional influence" in main group patients (80.90 ± 0.26 and 82.6 ± 0.19, respectively).Conclusion. Simultaneous bilateral mini-PCNL is safe and effective in well-selected patients.